Effect of selected elastic band resistance training on serum levels of fibroblast growth factor 23, TNF-α and hsCRP in overweight elderly women - Akbar Azamian Jazi; Esmaeil Moradi Sarteshnizi; Mahshid Fathi (Mashhad University of Medical Sciences, 2021)
ntroduction: Chronic inflammation can be the main cause of many common diseases in old age. Elevated level of CRP and proinflammatory cytokines such as TNF-α is positively associated with fibroblast growth factor 23 (FGF23). Therefore, considering the potentially beneficial effect of elastic band resistance training (EBRT) on these variables, this study was performed with aim to investigate the effect of 12 weeks of selected EBRT on serum levels of FGF23, TNF-α and hsCRP in overweight elderly women. Methods: This clinical trial study was performed in 2017 on 28 elderly women in Shahrekord.  The subjects were randomly divided into experimental and control groups. EBRT was performed for 12 weeks. Fasting blood samples were taken 24 hours before the first training session and 48 hours after the last training session to measure serum levels of FGF23, TNF-α and hsCRP. Data were analyzed by SPSS software (version 25) and repeated measure two-way ANOVA test. P<0.05 was considered statistically significant. Results: EBRT had no significant effect on serum FGF23 levels, BMI, and Waist-to-hip ratio in elderly women (P>0.05); but serum levels of TNF-α (P=0.046), hsCRP (P=0.037), and also body fat percentage (P=0.023) significantly decreased after EBRT. Conclusion: Regardless to no significant changes in FGF23 levels, it seems that 12 weeks of EBRT can have a significant effect on reducing chronic inflammation in the elderly by reducing the levels of hsCRP and proinflammatory cytokine TNF-α.